THE IMPACT OF 5G TECHNOLOGY ON DIGITAL MARKETING AND E-COMMERCE ECOSYSTEMS - Henny Noviany; Axelon S Renyaan; Johni Eka Putra (CV. Adiba Aisha Amira, 2024)
5G or fifth-generation mobile networks holds the promise of higher data rates, low latency, and more data traffic than earlier generations of mobile telecommunications technologies. Its relevance to both digital marketing and the e-commerce industry is such that there is a great shift in the conduct of online marketing of goods and services by businesses, as well as in the conduct of users of the digital space such as online and mobile transactions. The digital marketing ecosystem consists of different tools, platforms, and techniques that help design, implement, and analyze advertising activities in the internet space. As a rule, e- commerce refers to trade and other commercial activities performed via the World Wide Web, including business to consumer (B2C) and business to business (B2B) as well consumer to consumer (C2C) sales. The depiction illustrates how the 5G technology shapes the perspective towards and the functioning of the digital marketing and e-commerce ecosystem center.